Larval development in the Pacific oyster and the impacts of ocean acidification: Differential genetic effects in wild and domesticated stocks. (26th August 2021) - Durland, Evan; De Wit, Pierre; Meyer, Eli; Langdon, Chris
Abstract: The adaptive capacity of marine calcifiers to ocean acidification (OA) is a topic of great interest to evolutionary biologists and ecologists. Previous studies have provided evidence to suggest that larval resilience to high p CO2  seawater for these species is a trait with a genetic basis and variability in natural populations. To date, however, it remains unclear how the selective effects of OA occur within the context of complex genetic interactions underpinning larval development in many of the most vulnerable taxa. Here we evaluated phenotypic and genetic changes during larval development of Pacific oysters ( Crassostrea gigas ) reared in ambient (~400 µatm) and high (~1600 µatm) p CO2 conditions, both in domesticated and naturalized "wild" oysters from the Pacific Northwest, USA. Using pooled DNA samples, we determined changes in allele frequencies across larval development, from early "D‐stage" larvae to metamorphosed juveniles (spat), in both groups and environments. Domesticated larvae had ~26% fewer loci with changing allele frequencies across developmental stages and <50% as many loci affected by acidified culture conditions, compared to larvae from wild broodstock. Functional enrichment analyses of genetic markers with significant changes in allele frequency revealed that the structure and function of cellular membranes were disproportionately affected by high p CO2 conditions in both groups. These results indicate the potential for a rapid adaptive response of oyster populations to OA conditions; however, underlying genetic changes associated with larval development differ between these wild and domesticated oyster stocks and influence their adaptive responses to OA conditions.